Biometric cryptosystem to secure smart object communications in the internet of things: DOI: 10.48129/kjs.11169 - Meraoumia, Abdallah; Amroune, Mohamed; Laimeche, Lakhadr; Bendjenna, Hakiml (Kuwait Journal of Science, 2022)
Smart cities are seen as one of the strengths of developed countries. Despite its novelty, it has attracted a lot of attention which has prompted major tech companies to invest in various aspects related to their design. In fact, the Internet of Things is the most important pillar of these cities, which makes it possible to connect almost everything, machines, animals, people¨O to the Internet and facilitate the interaction between them. Like any electronic application, the security aspect is one of the most difficult challenges in the creation and design of such networks. We have therefore tried in this paper to propose a secure IoT framework based on cloud computing. In this study, we focused on the security aspect of a person’s connection to their objects using biometric cryptosystems. Our proposed cryptosystem uses the concepts of a chaotic system combined with hand-palm biometrics. In this study, oriented Basic Image Features (oBIF) is used as a feature extraction method. Subsequently, the user message is encrypted using the AES algorithm, whereas the user template is encrypted by a proposed algorithm.